Bioassay Directed Isolation, Biological Evaluation and in Silico Studies of New Isolates from Pteris cretica L. - Saleem, Farooq; Mehmood, Rashad; Mehar, Saima; Khan, Muhammad Tahir Javed; Khan, Zaheer-ud-Din; Ashraf, Muhammad; Ali, Muhammad Sajjad; Abdullah, Iskandar; Froeyen, Matheus; Mirza, Muhammad Usman; Ahmad, Sarfraz (MDPI, 2019)
Members of genus Pteris have their established role in the traditional herbal medicine system. In the pursuit to identify its biologically active constituents, the specie Pteris cretica L. (P. cretica) was selected for the bioassay-guided isolation. Two new maleates (F9 and CB18) were identified from the chloroform extract and the structures of the isolates were elucidated through their spectroscopic data. The putative targets, that potentially interact with both of these isolates, were identified through reverse docking by using in silico tools PharmMapper and ReverseScreen3D. On the basis of reverse docking results, both isolates were screened for their antioxidant, acetylcholinesterase (AChE) inhibition, α-glucosidase (GluE) inhibition and antibacterial activities. Both isolates depicted moderate potential for the selected activities. Furthermore, docking studies of both isolates were also studied to investigate the binding mode with respective targets followed by molecular dynamics simulations and binding free energies. Thereby, the current study embodies the poly-pharmacological potential of P. cretica. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.